Withinplant migration of the predatory mite Typhlodromalus aripo from the apex to the leaves of cassava: response to daynight cycle, prey location and prey density - Onzo, A.; Hanna, R.; Sabelis, M.W. (Springer, 2009)
Under attack by herbivores, plants produce a blend of“herbivore-inducedplant volatiles (HIPV)”that help natural enemies of herbivores locating their prey,thereby helping plants to reduce damage from herbivory. The amount of HIPVemitted by plants increases with herbivore density and is positively correlated withthe intensity of the olfactory response of natural enemies. In this study, wedetermined the effects of density or within-plant distribution of the herbivorous miteMononychellus tanajoaon movement of the predatory miteTyphlodromalus aripoout of apices of cassava plants. Proportions ofT. aripothat migrated out of apex, anddistances traveled were significantly higher whenM. tanajoawas further away fromthe apex—i.e. on middle or bottom leaves of cassava plants—than when present ontop leaves, or absent from the plant. This supports previous field observations thatT.aripois not a sit-and-wait predator but uses HIPV to search and locate its preywithin cassava plant.